The state of circulation policies and practices in Chinese academic libraries. (September 2019) - Kang, Qi; Wang, Pianran; Wang, Qing
The circulation service is an important, traditional library service. Circulation policies are the rules that govern borrowing and renewing materials and the penalties for overdue, lost, or damaged items. Some studies have reported the circulation policies of major academic libraries; however, literature documenting the borrowing privileges of Chinese libraries is scant and does not fully disclose its current characteristics and status. This study aims to investigate and explore the status, features, and patterns of circulation policies employed in the top 46 Chinese university libraries. The results indicated that circulation practices vary among libraries but common trends exist, including lengthened checkout and renewal period or unlimited borrowing length, increased number of items and no overdue fines or blocks on accounts until items are returned, or volunteer service, or online examination of library rules and regulation, or establishment of amnesty days regarding overdue procedures. Along with adding to the Chinese academic library services research field, these findings provide valuable directions for library policy improvements.